(3efJgi GdCZQGV aj Yde TaGA GdCeQGVs - (3jhMfG (B((3Mfjf(B) (3YfMhQj, J fMh (B1260(3g` (B1845(3es
(3ChdgG (B:s
(3ChdgG(B: (3SHMGfc eHQF Gdceg hGdCHQU heMjj GdehJi, eHOA CWhGQ GdcGFfGJ (B... (3jfHZj Cf jYde Cf GUWdGM cJH GdWH GdBf aj JQJjH GdCeQGV NdGa GUWdGM GdcJH GdbOjeIs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG GfJbGY GdhLg hGddYGH GdfgOj ajchfGf aj GdGSJjQHG ZjQ eHjf YfgG HGdcdjI HNdGageG aj GdUQY aEfgeG ef UaGJg hCeG GdJTfLGJ GdYGeI aajgG TjAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 210s
(3EjVGM Gdecfhf, L (B2: 571s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs